2007
DOI: 10.1111/j.1747-0285.2007.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Compensating Enthalpic and Entropic Changes Hinder Binding Affinity Optimization

Abstract: A common strategy to improve the potency of drug candidates is to introduce chemical functionalities, like hydrogen bond donors or acceptors, at positions where they are able to establish strong interactions with the target. However, it is often observed that the added functionalities do not necessarily improve potency even if they form strong hydrogen bonds. Here, we explore the thermodynamic and structural basis for those observations. KNI-10033 is a potent experimental HIV-1 protease inhibitor with picomola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(196 citation statements)
references
References 40 publications
6
187
0
3
Order By: Relevance
“…29 Recent studies of HIV-1 protease inhibitors have found that a slight modification to the structure of a ligand can lead to completely different thermodynamic profiles. 36 The previous suggestion that minor groove-binding could be mainly entropically driven was based on a limited number of examples and was qualified by the need to critically test the hypothesis by expanding the database of thermodynamic data for minor groove binders. The studies detailed here for thiazotropsin A provide important new insights into this process and indeed extend the thermodynamic database, considerably adding to the significance of our findings in this work.…”
Section: 30mentioning
confidence: 99%
“…29 Recent studies of HIV-1 protease inhibitors have found that a slight modification to the structure of a ligand can lead to completely different thermodynamic profiles. 36 The previous suggestion that minor groove-binding could be mainly entropically driven was based on a limited number of examples and was qualified by the need to critically test the hypothesis by expanding the database of thermodynamic data for minor groove binders. The studies detailed here for thiazotropsin A provide important new insights into this process and indeed extend the thermodynamic database, considerably adding to the significance of our findings in this work.…”
Section: 30mentioning
confidence: 99%
“…However, introducing H-bond donors or acceptors to establish stronger protein-ligand interactions often results in the absence of net gain in binding affinity [19,28]. Rather than targeting protein-ligand interactions per se, H-bonds are also reported to promote ligand binding affinity by displacing protein-bound water molecules into the bulk solvent [29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…However, retrospective analyses [1] have shown that a rational modification often only leads to a moderate improvement in DG bind , due to a compensation of the enthalpy (DH) and the entropy (DS). A shift from mainly entropically driven binding towards mainly enthalpically driven binding, or vice versa, is commonly observed [2][3][4]. This phenomenon is largely due to the current trend to optimise ligands for more enthalpic binding.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (4) implies that DS may be obtained from a linear regression over multiple DA estimates at different temperatures, obtained using, for example, TI. The third approach estimates DS directly from TI [8], using Eq.…”
Section: Theorymentioning
confidence: 99%